The mediating effect of market orientation on the relationship between entrepreneurial orientation dimensions and organizational performance: a study on banks in Libya - Faiz, Gaboul Ahmed; Ahmad, Fais; Al-Swidi, Abdullah Kaid (Pak Publishing Group, 2015)
The main purpose of this study was to investigate the mediating effect of Market Orientation (MO) on the relationship between entrepreneurial orientation dimensions (EO) namely: Innovativeness, Proactiveness, Risk-taking and organizational performance (OP). The motivation for this study was driven by the inconsistent findings in the literature concerning the relationships between EO, and organizational performance.Due to the inconsistent results, a new research has emerged and this has prompted further investigation on the effect of other variables that may better explain the nature of these links. In the related literature, many theories have suggested that the compatibility between strategies, resources, and capabilities as the keys for success. Questionnaires were distributed to 400 Sections of the Libyan banks.230 questionnaires were returned and used in the analysis using the PLS-SEM. The results of this study revealed that EO dimensions were positive and have also been proven to be significant predictors of organizational performance. More importantly, the results have also confirmed the mediating effect of Market Orientation on the relationships between EO dimensions, and organizational performance.